Investigation of electro-optical properties in bistable liquid crystal films doped with CsxWO3 nanorods. Issue 14 (14th November 2022) - Zhang, Yongming; Zhao, Xiangrong; Zhao, Yang; Guo, Zhun; Gao, Jianjing; Ma, Chen; Zhao, Yuzhen
ABSTRACT: It is of great practical significance to develop efficient and reversible bistable liquid crystal films. This work provides a multiple phase-shift controllable liquid crystal film containing tungsten bronze (Csx WO3 ) nanorods (NRs) and cholesteric liquid crystal, which can reversibly control the phase-shift via electric field, temperature or near infrared light. The Csx WO3 NRs were coated by polyvinylpyrrolidone (PVP) layer, and the Csx WO3 /PVP NRs could form a compatible NIR-absorbing film, which could generate heat to switch LC film from planar texture to focal conic texture. The bistable liquid crystal film could save almost 53% time at thermal elimination compared to LC mixture without NIR absorbent when the content of Csx WO3 /PVP NRs reaches 0.8%. The functional bistable liquid crystal films reported in this paper expand the application field of bistable liquid crystal display. GRAPHICAL ABSTRACT: uf0001